2020
DOI: 10.1507/endocrj.ej19-0409
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in medullary thyroid microcarcinomas

Abstract: The aim of this prospective study was to analyze accuracy of sentinel lymph node biopsy with methylene blue dye for intraoperative detection of lateral metastases in clinically N0M0 medullary microcarcinomas with calcitonin <1,000 pg/mL and selection of true-positive patients for one-time therapeutic lateral dissection. In addition to total thyroidectomy and central neck dissection, all patients had bilateral sentinel biopsy of jugulo-carotid regions after methylene blue injection to decide upon necessity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…For MTC patients, adjuvant therapy is of limited value. Surgical resection is the cornerstone of treatment and aims to achieve loco-regional control and, if possible, curation [ 20 , 32 ]. Patients who are biochemically cured with normal basal calcitonin levels after intended curative dissection have a 10-year survival rate of 97.7% [ 20 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For MTC patients, adjuvant therapy is of limited value. Surgical resection is the cornerstone of treatment and aims to achieve loco-regional control and, if possible, curation [ 20 , 32 ]. Patients who are biochemically cured with normal basal calcitonin levels after intended curative dissection have a 10-year survival rate of 97.7% [ 20 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…SLN biopsy in MTC has been investigated in a few studies [ 25 27 , 32 ]. Puccini et al performed the SLN procedure using preoperative lymphoscintigraphy and intraoperative gamma probe and found micrometastases in 3 of 4 cT1N0 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Focussing on those papers on SLN detection with the highest number of patients, in 2010 Cunningham et al examined 211 PTC patients using 1% isosulphan blue with a detection rate (DR) of 91%; in 2006 Rubello et al used patent blue V in 153 PTC cases with a DR of 69%; in 2020 I. Markovic et al used methylene blue in 153 PTC patients with a DR of 91.8% ( 62–64 ). Using methylene blue in 20 MTC patients, in Santrac et al ( 65 ) achieved a DR of 100%, with 10% positive for metastasis. In Wang et al ( 66 ) described the use of indocyanine green (ICG) with methylene blue for detecting SLN in 45 micro-PTC patients with a longer operative time but a lower rate of hypoparathyroidism: the authors concluded that for SLN in TC ICG in combination with methylene blue is feasible, safe and also clinically significant for protection of the parathyroids.…”
Section: Sln Procedures In Tcmentioning
confidence: 99%
“…With the VD method at surgery, the vital blue dye intra-or peritumoral injection is performed generally utilizing a tuberculin syringe (24,62,(64)(65)(66)(67). The authors recommend not mobilizing the thyroid before injection to ensure intact lymphatic drainage.…”
Section: Sln Procedures In Tcmentioning
confidence: 99%
“…Methylene blue (MB) is cytological stain that has demonstrated affinity to cancer [ 25 , 26 ]. It is approved for several clinical applications by the United States Food and Drug Administration [ 27 , 28 ] and there is a progressively increasing number of publications focused on MB in the context of thyroid oncology-based problems [ 29 , 30 , 31 , 32 ]. Recent reports have demonstrated that fluorescence polarization (Fpol) of MB is significantly elevated in cancerous human breast ductal carcinoma and glioblastoma cell lines [ 33 , 34 ], and in malignant renal FNAC specimens [ 35 ].…”
Section: Introductionmentioning
confidence: 99%